2017
DOI: 10.1371/journal.pone.0179838
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors associated with ART adherence and retention in care under Option B+ strategy in Malawi: A qualitative study

Abstract: Although several studies have documented challenges related to inadequate adherence to antiretroviral therapy (ART) and high loss to follow-up (LTFU) among Option B+ women, there is limited understanding of why these challenges occur and how to address them. This qualitative study examines women’s experiences with ART adherence and retention in care. Between July and October 2015, in-depth interviews were conducted with 39 pregnant and lactating women who initiated ART at Bwaila Hospital in Lilongwe, Malawi. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
47
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 41 publications
10
47
2
1
Order By: Relevance
“…Among the personal factors, non-supportive or abusive spousal behaviour was frequently reported as a crucial factor associated with LTFUs, consistent with findings from other studies [10][11][12][13][14]32 . Men are considered to be the primary decision makers regarding family matters, not only in Malawi but also many parts of Sub-Saharan Africa 11 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the personal factors, non-supportive or abusive spousal behaviour was frequently reported as a crucial factor associated with LTFUs, consistent with findings from other studies [10][11][12][13][14]32 . Men are considered to be the primary decision makers regarding family matters, not only in Malawi but also many parts of Sub-Saharan Africa 11 .…”
Section: Discussionsupporting
confidence: 90%
“…In our study, shortage of health commodities; and inadvertent disclosure of HIV status by health care workers were not reported as causes of LTFU despite being reported in other studies [12][13][14]22,23 . This is good news as resource allocation and ensuring constant supply of HIV supplies is backbone in diagnosis and control of spread of HIV through viral suppression.…”
Section: Discussioncontrasting
confidence: 77%
“…This is in line with findings of other study done in Ethiopia revealed that health workers are not happy to handle deliveries for women who are known HIV positive due to fear of accidental infection [22]. Other studies have also had similar findings [17,23,[28][29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this study revealed that mother support groups are facilitator of PMTCT service utilization. The findings also similar with other studies in Malawi reported that promotion of peer counseling schemes for PMTCT [30]. This indicated that mother support group served as peer educators in health facilities to provide education and psychosocial support to HIV positive pregnant and lactating women promotes PMTCT service utilization.…”
Section: Discussionsupporting
confidence: 89%
“…PMTCT treatment than women who tested positive during pregnancy [24]. In a qualitative study, Gugsa et al identified Improved counseling at initiation, active follow-up counseling, women's economic empowerment interventions, promotion of peer counseling schemes as measures to improve adherence [25]. The hypothesis of the contribution of the strong desire of a HIV free newborn not to repeat the stigma raised above for the coming child, the free of charge antiretroviral drug taken once daily, the relatively short duration of pregnancy window observance assessment as compared to lifelong observance assessment and the therapeutic education aimed at strengthening observance as factors explaining this adherence not assessed in this study are to be confirmed…”
Section: Discussionmentioning
confidence: 99%